Early immune suppression leads to uncontrolled mite proliferation and potent host inflammatory responses in a porcine model of crusted versus ordinary scabies. - Sajad A Bhat; Shelley F Walton; Tomer Ventura; Xiaosong Liu; James S McCarthy; Stewart T G Burgess; Kate E Mounsey (Public Library of Science (PLoS), 2020)
Scabies is a neglected tropical disease of global significance. Our understanding of host-parasite interactions has been limited, particularly in crusted scabies (CS), a severe clinical manifestation involving hyper-infestation of Sarcoptes scabiei mites. Susceptibility to CS may be associated with immunosuppressive conditions but CS has also been seen in cases with no identifiable risk factor or immune deficit. Due to ethical and logistical difficulties with undertaking research on clinical patients with CS, we adopted a porcine model which parallels human clinical manifestations. Transcriptomic analysis using microarrays was used to explore scabies pathogenesis, and to identify early events differentiating pigs with ordinary (OS) and crusted scabies. Pigs with OS (n = 4), CS (n = 4) and non-infested controls (n = 4) were compared at pre-infestation, weeks 1, 2, 4 and 8 post-infestation. In CS relative to OS, there were numerous differentially expressed genes including pro-inflammatory cytokines (IL17A, IL8, IL19, IL20 and OSM) and chemokines involved in immune cell activation and recruitment (CCL20, CCL27 and CXCL6). The influence of genes associated with immune regulation (CD274/PD-L1 and IL27), immune signalling (TLR2, TLR8) and antigen presentation (RFX5, HLA-5 and HLA-DOB) were highlighted in the early host response to CS. We observed similarities with gene expression profiles associated with psoriasis and atopic dermatitis and confirmed previous observations of Th2/17 pronounced responses in CS. This is the first comprehensive study describing transcriptional changes associated with the development of CS and significantly, the distinction between OS and CS. This provides a basis for clinical follow-up studies, potentially identifying new control strategies for this severely debilitating disease.